2023
DOI: 10.1038/s41598-023-30090-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mammalian sex hormones on in vitro organogenesis of common bean (Phaseolus vulgaris L.)

Abstract: Beans are an important plant species and are one of the most consumed legumes in human nutrition, especially as a protein, vitamin, mineral, and fiber source. Common bean (Phaseolus vulgaris L.) is a plant that also has an important role in natural nitrogen fixation. Currently, in vitro regeneration and micropropagation applications are limited in relation to genetic factors in bean Accordingly, there is great need to optimize micropropagation and tissue culture methods of the bean plant. To date, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our result indicated that the highest mean value of the types of explants undergoing morphogenesis was obtained in plumule but the lowest was obtained in the radicle explant. Our results con rm with ndings of Haliloğlu et al (2023). The plumule explant divides actively and rapidly in the presence of exogenous MSH in the medium with result of generating multiple root and shoots.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our result indicated that the highest mean value of the types of explants undergoing morphogenesis was obtained in plumule but the lowest was obtained in the radicle explant. Our results con rm with ndings of Haliloğlu et al (2023). The plumule explant divides actively and rapidly in the presence of exogenous MSH in the medium with result of generating multiple root and shoots.…”
Section: Discussionsupporting
confidence: 90%
“…For this reason, it is important to conduct studies on the use of MSHs on plants and to reveal the effects of these hormones on plant growth in vitro. Previously, MSHs and their concentrations have been developed for in vitro grown of some plants, such as wheat (Turkoglu 2022) and bean (Haliloğlu et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies on plants are vital for agriculture, plant science, and biotechnology, enhancing cultivation, biodiversity conservation, and sustainability [20][21][22][23][24]. Developing species-specific tissue culture methods is essential due to variations in plant species [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies on the existence of MSHs in plants has increased, prompting the need to investigate the role these hormones play in plant life [9]. Recent studies have focused on evaluating the effects of exogenous application of these compounds on plant growth and development, as well as their tolerance to various abiotic and biotic stimuli and their metabolic mechanism of action [10,11].…”
Section: Introductionmentioning
confidence: 99%